PROBLEM BASED LEARNING AS A STRATEGY FOR DEVELOPING CIVIC DISPOSITION OF STUDENTS (International Journal of Cultural and Social Science, 2026)
This study aims to describe the implementation of the Problem Based Learning (PBL) model in science and social studies (IPAS) learning and to analyze the process of developing students’ civic disposition through problem- based learning in elementary school. The research was conducted at SD Negeri 1 Mojosongo, Boyolali Regency, using a qualitative descriptive approach with a case study strategy. The research subjects consisted of third- grade and fifth-grade teachers, students, and the school principal. Data were collected through observation, in-depth interviews, and documentation. Data validity was ensured through technique triangulation and source triangulation. The findings revealed that the implementation of PBL was carried out systematically through stages of problem orientation, student organization, investigation, data analysis, presentation, and reflection. The process of developing civic disposition occurred gradually through contextual and collaborative learning experiences. The aspects of civic disposition that developed included social responsibility, environmental awareness, collaboration skills, active participation, empathy, and democratic attitudes. Observation results showed that responsibility, communication, active participation, and empathy were categorized as excellent, while environmental awareness and collaboration were categorized as good. The study concludes that Problem Based Learning is effective as a strategy for developing civic disposition among elementary school students because it integrates cognitive, affective, and social dimensions within the learning process.